The School Years Screening Test for Evaluation of Mental Status-Revised (SYSTEMS-R) as a cognitive function screening tool in children with epilepsy - Urfianty, Urfianty; Pusponegoro, Hardiono Djuned; Alatas, Fatima Safira; Soebadi, Amanda; Ramli, Yetty (Indonesian Pediatric Society, 2024)
Background Children with epilepsy are at high risk of cognitive impairment that can affect quality of life. Intelligence quotient (IQ) measurement using the Wechsler Intelligence Scale for Children (WISC) is the gold standard test of cognitive function, but it is time-consuming and costly. The School Years Screening Test for Evaluation of Mental Status-Revised (SYSTEMS-R) is a potential cognitive function screening tool that can be used in children with epilepsy. Objective To assess the performance of SYSTEMS-R as a cognitive function screening tool in children aged 6-15 years with epilepsy. Methods This cross-sectional diagnostic test study was conducted in children aged 6-15 years with epilepsy. All subjects were assessed using both SYSTEMS-R and WISC 4th edition. The sensitivity, specificity, positive and negative predictive value, likelihood ratios of the positive and negative tests, and accuracy of SYSTEMS-R was calculated, with WISC as the gold standard test. Results Based on the SYSTEMS-R, the prevalence of cognitive impairment in children aged 6-15 years with epilepsy in our population was 86.4%. With WISC as the gold SYSTEMS-R had 84% sensitivity, 91% specificity, 98% positive predictive value, and 47% negative predictive value. The likelihood ratio of a positive SYSTEMS-R test was 10.11 and the likelihood ratio of a negative test was 0.17. The overall accuracy of SYSTEMS-R to detect cognitive impairment was 85%. Conclusion SYSTEMS-R has good sensitivity and specificity to assess cognitive function in children 6-15 years with epilepsy. It can be considered for widespread use in the early detection of cognitive impairment in pediatric epilepsy patients aged 6-15 years.